Connotations of the Straightforward Colours in the Holy Quran - Al Bzour, Salahaldeen Mohammad (American Journal of Humanities and Social Sciences, 2015)
Colours are like words express particular or general meanings such as the colours in the traffic lights. Quran mentioned the most common colours because of the multi-faceted roles that they convey, both in sensual or moral purposes, as well as their aesthetic values. The analytical method has been adopted in this research that attempts, as much as possible; to make use of statistical analysis of colours' denotations as mentioned in the Quranic verses. Anyway, the purpose of this research is to explore and to bring out the implicit denotations of the straightforward colours in the Holy Quran as well as to highlight the ability of the colours in affecting the psyche. The results show that colours are used in order to confirm God’s inimitability in the diversity of the colours of His creatures. They also show that psyche can be affected by the colours such as black and white. In addition to, the results reveal that the colours are sometimes used to tell about the future definitely in the Day of Resurrection and in the Paradise such as white. Furthermore, the results show that the importance of the colours rely in their moral lessons.